2020
DOI: 10.15562/bmj.v9i3.2023
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics of non-operative anterior cruciate ligament injury associated with poor knee functions on activities of daily living: a cross-sectional study

Abstract: Introduction: The ACL injury has commonly occurred in a greater number of athletes, less publication is about poor knee function and ACL injury in the patient with non-operative treatment. This study aimed to describe the characteristics of patients with ACL injury non-operative, which are associated with poor knee function on daily living activities.Methods: We included patients with ACL injury that has been diagnosed for ACL injury by an orthopedic surgeon or physiotherapist in a hospital or private clinic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The results of this study showed that the general characteristics of patients with lateral ligament injury included younger participants of younger than 40 years old. This is similar to previous study conducted by Adhitya I et al, who showing the mean age of patients with lateral ligament injuries was 27.5 years old (SD=6.6) [20] . Moreover, most of the participants were males and among body mass index of higher than 25 Kg/m2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that the general characteristics of patients with lateral ligament injury included younger participants of younger than 40 years old. This is similar to previous study conducted by Adhitya I et al, who showing the mean age of patients with lateral ligament injuries was 27.5 years old (SD=6.6) [20] . Moreover, most of the participants were males and among body mass index of higher than 25 Kg/m2.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, most of the participants were males and among body mass index of higher than 25 Kg/m2. This is similar to the results of Adhitya I et al who found that 89.3 % the patients with lateral ligament injuries were males [20] . This difference between the two genders could be because of the morphology of the knee joint between sexes which had an important role in the risk of injury.…”
Section: Discussionsupporting
confidence: 92%
“…Data were extracted from 242 studies (7 RCTs, 235 observational/cohort), including 123 687 participants (43% females/ women/girls, mean age 26 years at ACL surgery), aged between 10 and 64 years at ACL injury or follow-up, most (94%) operatively managed, and follow-up ranged from 2 months to 31 years post-ACL injury/ACLR (online supplemental appendix 7). Notably, only 13 studies included an exclusively non-operatively managed group [36][37][38][39][40][41][42][43][44][45][46][47][48] ; however, 25 studies reported preoperative (7 meta-analyses) data. Six studies included both operatively and non-operatively managed individuals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…2 ACL injuries are among the common injuries in the young adult population. 3,4 The annual incidence of ACL injuries in the general population reaches 68.6 per 100,000 people. 2,5 Management of patients with ACL injuries can include non-invasive approaches and surgery.…”
Section: Introductionmentioning
confidence: 99%